Risk Factors for Decompression Sickness - Fitriasari, Elsye; Sri Dewi Untari, Ni Komang; Annisa Fitra, Nasywa (Riviera Publishing, 2024)
Over the past few decades, self-contained underwater breathing apparatus (SCUBA) diving has gained popularity globally. Efforts to explore new trails underwater have rapidly expanded recreational, technical, professional, and military diving opportunities. Decompression sickness (DCS) is an essential and complex health problem among divers, stemming from changes in environmental pressure during and after underwater travel. Understanding the various risk factors associated with DCS is critical in implementing safe diving practices. Medical professionals, regardless of specialization, need to be aware of the adverse effects of changes in exposure to environmental stresses on the human body. Decompression sickness (DCS) can occur quickly, immediately, or very mildly and is delayed. Divers with DCS can arrive late, far from the dive site, due to their varied presentation, slow start, and air travel after diving. Medical personnel must consider the previous days' activities and be aware of diving problems and disorders to take advantage of the opportunity to diagnose and treat such patients appropriately. Individual and environmental risk factors play a role in increasing the incidence of DCS in divers, including obesity, smoking, alcohol, anxiety disorders, comorbidities, previous injuries, cold water, duration, and depth of diving. A comprehensive understanding of these multifaceted risk elements is essential for divers and medical professionals. Armed with this knowledge, they can better assess potential risks, adopt proactive precautions, and ensure diver safety, ultimately reducing severe DCS incidents.